SONG LYRICS AS A STIMULAN MEDIA IN WRITING SHORT STORIES FOR JUNIOR HIGH SCHOOL STUDENTS - Fauzi Rahman; Supatmi Supatmi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: The song is a work favored by all humans in the world. Songs can be enjoyed by allpeople, including teenagers who are still active in school. Because it is related to imagination,songs can certainly be a good medium when applied in the learning process in the classroom,especially in writing short stories. Therefore, this study aims to determine the effectiveness of songmedia in stimulating the ability to write short stories in students. This research is a quantitativeresearch with Cluster Sampling method (group sample). This study used a posttest-only controlgroup design, with the two groups: experimental class and control class which only final testresults were taken (post test). The population in this study were students at one of the junior highschools in Jakarta, Indonesia (51 students). 25 students were positioned as the control class and 26students as the experimental class. The results showed that the ability to write short stories throughsong media was effective in stimulating the ability to write short stories. This is based on theresults of the t-test, found t-count=2.73 and t-table = 2.01. Because t-count is greater than t-table,then Ho is rejected, it can be concluded that the average learning outcomes of writing short storiesthat use song media are higher than the average learning outcomes of writing short stories that donot use song media.Key Words: Song Lyrics, Short Stories, Writing, Junior High School.